Assessment of the compensation point of Cirsium arvense and effects of competition, root weight and burial depth on below‐ground dry weight – leaf stage trajectories. (4th June 2018) - Verwijst, T; Tavaziva, V J; Lundkvist, A
Summary: Farmers are recommended to employ mechanical control when Cirsium arvense is most sensitive to disturbance. Earlier studies suggest that this occurs at a stage of minimum below‐ground dry weight, coinciding with three to seven or seven to ten leaves per shoot, depending on the definition of below‐ground dry weight. However, some farmers notice better effects when mechanical control is performed at earlier leaf stages. To estimate the compensation point (CP), defined as the minimum weight of the entire below‐ground structure of C. arvense and to further understand links between initial root weight, planting depth and crop competition, three outdoor pot experiments were performed in Sweden in 2013‐2014. We hypothesised that (i) CP likely occurs before C. arvense has developed three leaves, (ii) relative depletion of the below‐ground system at CP is less at lower initial root weight compared with higher weight, and (iii) methodological variations in CP estimations have minor impact on the results. We found that the CP for C. arvense in all treatments occurred before shoots had developed three leaves and that treatment effects were minor (<0.5 leaf stages). Leaf and leaf stage definitions, choice of leaf range and model also had minor effects on CP estimates. Depletion of planted root fragments ceased around leaf stages 3‐4, and their partial replenishment also constitutes evidence for a CP at early leaf stages. For agronomy, our results imply that mechanical control of C. arvense should be performed earlier than previously recommended, probably before reaching an average of three to four leaves per shoot.